Physical Education in high school: focus on production Brazilian scientific (Research, Society and Development, 2022)
The present research, characterized as a systematic review, analyzed the scientific production on Brazilian School Physical Education in High School. The search for production took place in the indexing databases Scielo, LILACS and Scopus, considering the descriptors in Portuguese Physical Education and High School, with the help of the boolean AND. At first, 253 articles were found, which were analyzed based on inclusion and exclusion criteria, ending with eight selected articles. From the analysis of the production found, it was observed that Physical Education in High School permeates the discussions about its relevance, its structuring as a school curriculum and the relationship of the contents proposed by the discipline with the life of the subject who is involved in this process. The data make it possible to conclude that there is a shortage of scientific production that portrays Physical Education in EM within the indexing bases chosen here, as well as that discussions about Physical Education as a curricular discipline need to relate their knowledge beyond the walls of the school, reporting meaning and meaning for the life of each student.